Why does patients’ discharge delay after vertebral augmentation? A factor analysis of 1,442 patients - Zhao, He; Zhang, Zhengping; Wang, Yanjun; Qian, Bing; Cao, Xinhao; Yang, Ming; Liu, Yangjin; Zhao, Qinpeng (Frontiers in Surgery, 2022)
Objective Vertebral augmentation techniques are widely used to treat osteoporotic vertebral compression fractures (OVCFs). Superior analgesic effects and shortened bed rest time means patients recover quickly, but prolonged unscheduled hospitalization can increase medical expenses and the risk of bed rest complications. The aim of this study was to investigate the reasons for prolonged hospitalization after vertebral augmentation surgery and to determine the relative risk factors. Methods A single-center retrospective study was conducted to enroll patients with OVCFs and accepted vertebral augmentation surgery from January 2017 to December 2017. Clinical information was collected from the Hospital Information System (HIS). The criterion of delayed discharge was postoperative hospitalization more than 3 days. Telephone interviews and medical history evaluations were conducted to confirm the exact reason for retention. The risk factors were analyzed by multiple logistic regression. Results Overall, 1,442 patients were included, and 191 (13.2%) stayed in the hospital for more than 3 days postoperatively. The reasons for delayed discharge were psychological factors (37.2%), residual pain (32.5%), cardiopulmonary complications (15.7%), nonspecific symptoms (8.4%), incision abnormalities (2.6%), thrombosis (2.1%), and postanesthesia reactions (1.6%). The multiple logistic model was significant; age (OR 1.028; 95% CI 1.009–1.046), preoperative stay (OR 1.192; 95% CI 1.095–1.298), operation type (OR 1.494; 95% CI 1.019–2.189), and the number of surgical segments (OR 2.238; 95% CI 1.512–3.312) showed statistical significance. In contrast, gender (P > 0.1) and chronic comorbidities (P > 0.1) were not predictors in this model. Conclusion Overall, 13.2% of OVCF patients who underwent vertebral augmentation surgery were not discharged within 3 days postoperatively, and several predictors were found. Preoperative communication and comprehensive evaluations are calling for more attention; physicians should adopt an appropriate medical process to enhance rehabilitation in geriatric orthopedics.